The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/00000542-200305000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Morbidity and Quality of Tracheal Intubation

Abstract: The quality of tracheal intubation contributes to laryngeal morbidity, and excellent conditions are less frequently associated with postoperative hoarseness and vocal cord sequelae. Adding atracurium to a propofol-fentanyl induction regimen significantly improved the quality of tracheal intubation and decreased postoperative hoarseness and vocal cord sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
265
4
25

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(304 citation statements)
references
References 40 publications
10
265
4
25
Order By: Relevance
“…The overall incidence of SLI at nasofibroscopic examination was low (less than 2%) and comparable to that reported by Baillard et al 1 These results contrast with the much higher incidence of vocal cord sequelae, reaching 42% in non-relaxed patients as previously reported by Mencke et al 5 These authors performed systematic examination of the vocal cords, before and after each anesthetic. For our study, we considered it to be more relevant to assess the incidence of SLI, rather than to record the overall rate of laryngeal sequelae, including non-symptomatic injuries.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The overall incidence of SLI at nasofibroscopic examination was low (less than 2%) and comparable to that reported by Baillard et al 1 These results contrast with the much higher incidence of vocal cord sequelae, reaching 42% in non-relaxed patients as previously reported by Mencke et al 5 These authors performed systematic examination of the vocal cords, before and after each anesthetic. For our study, we considered it to be more relevant to assess the incidence of SLI, rather than to record the overall rate of laryngeal sequelae, including non-symptomatic injuries.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we chose to perform nasofibroscopic examination, only for those patients who were continuing to suffer from laryngeal symptoms 48 hr to 30 days after anesthesia. This protocol discrepancy can explain, in part, the lower incidence of laryngeal damage which we report, compared to the observations of Mencke et al 5 Furthermore, the use of smaller tracheal tubes (6.5 and 7 mm), compared to the larger tube sizes used in the study by Mencke et al 5 (7.5 mm for women) may also have contributed to the incidence of laryngeal damage. The size of endotracheal tube contributes significantly to the occurrence of laryngeal morbidity.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Supplementing a propofol-opioid induction regimen with a non-depolarizing agent improves the quality of tracheal intubation and decreases postoperative hoarseness. 17 . It has been previously demonstrated that rocuronium 0.3 mg Á kg -1 with propofol and an opioid allows adequate intubating conditions.…”
Section: Discussionmentioning
confidence: 99%